The [C II]/[N II] ratio in 3 < z < 6 sub-millimetre galaxies from the South Pole Telescope survey - Cunningham, D. J. M.; Chapman, S. C.; Aravena, M.; de Breuck, C.; Béthermin, M.; Chen, Chian-Chou; Dong, Chenxing; Gonzalez, A. H.; Greve, T. R.; Litke, K. C.; Ma, J.; Malkan, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
International audience We present Atacama Compact Array and Atacama Pathfinder Experiment observations of the [N II] 205 μm fine-structure line in 40 sub-millimetre galaxies lying at redshifts z = 3-6, drawn from the 2500 deg 2 South Pole Telescope survey. This represents the largest uniformly selected sample of high-redshift [N II] 205 μm measurements to date. 29 sources also have [C II] 158 μm line observations allowing a characterization of the distribution of the [C II] to [N II] luminosity ratio for the first time at high redshift. The sample exhibits a median L $_{{\rm{[C\,{\small II}]}}}$ /L $_{{\rm{[N\,{\small II}]}}}$ ≍ 11.0 and interquartile range of 5.0 -24.7. These ratios are similar to those observed in local (Ultra)luminous infrared galaxies (LIRGs), possibly indicating similarities in their interstellar medium. At the extremes, we find individual sub-millimetre galaxies with L $_{{\rm{[C\,{\small II}]}}}$ /L $_{{\rm{[N\,{\small II}]}}}$ low enough to suggest a smaller contribution from neutral gas than ionized gas to the [C II] flux and high enough to suggest strongly photon or X-ray region dominated flux. These results highlight a large range in this line luminosity ratio for sub-millimetre galaxies, which may be caused by variations in gas density, the relative abundances of carbon and nitrogen, ionization parameter, metallicity, and a variation in the fractional abundance of ionized and neutral interstellar medium.